Analisa Kualitas Air Sumur Pemukiman Kumuh Gampong Beurawe Kota Banda Aceh - Bahagia Bahagia; Irda Yunita; Ruslin Ruslin (Jurnal Serambi Engineering, 2018)
This study aims to analyze the level of water pollution, the factors causing water pollutionand to know how to minimize the level of water pollution wells in Gampong Beurawe Kuta AlamDistrict Banda Aceh. Water quality analysis in this research was conducted by comparing parametersmeasured with water quality standard parameters in accordance with the provisions of Minister ofHealth Regulation No. 492 / Menkes / Per / IV / 2010 on the Terms of Water Quality. The sample ofthis research is well water taken in 5 hamlets (A, B, C, D and E) in Gampong Beurawe Kuta AlamSub-district for 5 samples (each 1 sample for each hamlet). The results of measurements on 5 samplesshowed that the well water was odorless, the standard temperature, normal color, TSS and E colidid not exceed the maximum standard of drinking water. For the total parameter of coliform, only 1hamlet is B hamlet which meet the standard that is equal to 47/100 ml. Dusun A, C, D and E, totalcoliform content did not meet the standard that is equal to 68, 70 and 86/100 ml, so that water wells in4 hamlets are not in accordance with Permenkes Number 492 / Menkes / Per / IV / 2010 about QualityTerms Clean water. Beurawe well water pollution is mostly caused by household wastewater, smallindustry and waste of trading activities